ANALISIS KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 2 DI SD YPK BUKIT SION KUADAS - Felda Margterh Mobilala; Muhammad Faizin; Muhamad Ali Kasri (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the analysis of early reading skills in second grade students at SD YPK Bukit Sion Kuadas. The purpose was to determine the early reading ability of the students in that school. The approach was descriptive qualitative using data collection techniques in the form of observation, interviews, and documentation. Data were analyzed through data collection steps such as data reduction, data presentation, and drawing conclusions. The results showed that the students' early reading ability was: students have difficulty identifying letters, changing words, pronouncing wrong words, stammering spelling, not understanding the contents of the reading, and having difficulty concentrating. The external factors that became the results of this study was the parents of students, they still lacked retraining at home to read. The student tends not to progress which results in the students not being able to read fluently. The role of parents in guiding in learning to read is very influential in improving children's early reading skills. The habit of learning to read should be more applied at home with simple methods in teaching, for example by using a short story book, or using colored alphabet cards as the teaching medium